Reduction of Sulfur Compounds from Petroleum Fraction Using Oxidation-Adsorption Technique - Ahmedzeki, Nada Sadoon; Ibrahem, Ban Jaber (Iraqi Journal of Chemical and Petroleum Engineering, 2015)
Oxidation of sulfur compounds in fuel followed by an adsorption process were studied using two modes of operation, batch mode and continuous mode (fixed bed). In batch experiment oxidation process of kerosene with sulfur content 2360 ppm was achieved to study the effect of amount of hydrogen peroxide(2.5, 4, 6 and 10) ml at different temperature(40, 60 and 70)°C. Also the effect of amount acetic acid was studied at the optimal conditions of the oxidation step(4ml H2O2 and 60 °C).Besides, the role of acetic acid different temperatures(40, 60, 70) °C and 4ml H2O2, effect of reaction time(5, 30, 60, 120, 300) minutes at temperatures(40,60) °C, 4ml H2O2 and 1 mlHAC) and effect of reaction temperature were studied. The results showed that the percentage removal of sulfur compounds increases with the increasing amount of hydrogen peroxide and amount of acetic acid also the percentage removal of sulfur compounds increases by addition acetic acid, reaction time up to 300 minutes and reaction temperature. In the fixed bed adsorption process, the oxidized kerosene having sulfur content being reduced to 939.28 ppm, was let to flow through a bed of 10Ni/ -Al2O3. The results showed that a sulfur removal of 95.38 % was obtained. By this the total sulfur removal of 98.38 % was obtained from the two consecutive processes. The resultant fuel had only 43.47 ppm. Also a study of the capability of the same bed to desulfurize raw feed of kerosene of 2360 ppm of sulfur compounds was investigated. 43.3% removal of sulfur compounds was achieved which reflects the catalytic properties of the adsorbent which could act as an oxidative adsorptive material. The results showed that by increasing feed flow rate, the breakthrough curve becomes steeper. Also the maximum removal of sulfur compounds was obtained in the case of bed height 20 cm and flow rate 0.3 l/h.